“Difusi dan Ideologi Bahasa: Analisis Wacana Kritis terhadap Situs Badan Bahasa” - Falah, Fajrul; Andriani, Merry; Fitriati, Anna; Tiani, Riris; Pratama, Rifka (Fakultas Ilmu Budaya Universitas Diponegoro, 2025)
This study departs from the view that Badan Pengembangan dan Pembinaan Bahasa website serves as a showcase for the national and international language. How does the website display and represent the image and value of the Indonesian language both domestically and abroad. The purpose of this study is to reveal the linguistic ideology and diffusion of language (terminology) through the digital media of official state institutions. The research method used is Norman Fairclough's critical discourse analysis (CDA), focusing on three dimensions of analysis, namely textual analysis (micro description), discursive practice (meso interpretation), and social analysis (macro-explanation). This study focuses on the features of BIPA, Penerjemahan Daring, and KBBI Daring on the website. The results of the study show that the features on the Badan Bahasa website represent Indonesian as a national identity and a means of diplomacy. These features are not merely a collection of data or terms, but play a role in spreading the ideology, hegemony, and legitimacy of Indonesian at the regional, national, and international levels. Although the language standardization efforts have been relatively successful, it is necessary to continuously update the data and evaluate its effectiveness in society. This study is limited to the study of language diffusion, and further in-depth research is needed through other approaches such as linguistic corpus, sociolinguistics, and comparative historical linguistics.